An observational retrospective study on safety and functional outcomes of arthroscopic anterior cruciate ligament reconstruction using Sironix suture button and interference screw - Mohammed, Murtuza Ahmed; Parameswaran, Apurve; Ponnala, Vinay Kishore; Eachempati, Krishna Kiran; Apsingi, Sunil; Moharana, Ashok Kumar; Angrish, Sachin; T. S., Deepak (International Journal of Research in Orthopaedics, 2023)
Background: Anterior cruciate ligament (ACL) injury is a persistent orthopaedic condition that affects a wide spectrum of people. ACL reconstruction (ACL-R) stands out as the primary treatment option. Graft fixation with suture buttons and interference screws has proven to be a highly successful and reliable method for ACL-R. In this context, our research aims to assess the safety and functional outcomes of patients who underwent arthroscopic ACL-R using the Sironix suture button and interference screw. Methods: This was a retrospective observational study. Patients who underwent arthroscopic ACL-R using Sironix suture button and interference screw (January 2018-March 2022) were included in the study. Functional outcomes of patients were evaluated using the international knee documentation committee (IKDC) assessment, the Tegner activity scale (TAS), the Lysholm knee scoring scale, the modified knee injury and osteoarthritis outcome score (KOOS) quality of life subscale, and the single assessment numerical evaluation (SANE) score. Adverse events, if any, were recorded. Results: All patients achieved excellent outcome measures for IKDC, Tegner, Lysholm, KOOS, and SANE scores. The mean (SD) IKDC score was 88.76 (7.16), Tegner activity score was 5.9 (1.13), while the Lysholm score was 96.9 (6.56). The overall KOOS score was 93.7 (7.52), and the overall SANE score for the affected joint was 94.5 (7.22). Conclusions: Arthroscopic ACL-R using Sironix implants (Helysis titanium interference screw, Helysis PLDLA+β-TCP interference screw, Infiloop fixed loop UHMWPE suture titanium button, Proloop adjustable loop UHMWPE suture Titanium button, and Titanium suture disc) demonstrated safety and good functional outcomes.